Radicalism and Revolution in Britain 1775-1848 - Davis, M. author. aut Link
XV, 242 p.
Keywords: The spectre of revolution and the nature of radicalism in Britain from the late eighteenth century through to the age of the Chartists has for some time engaged the interest of scholars and been the topic of much debate. This book honours one of the subject's most renowned and respected historians, Professor Malcolm I. Thomis. In a collection distinguished by its formidable range of contributors, a series of stimulating essays explores and re-examines the threats and ideas of revolution and the byzantine networks and character of British radical culture in the turbulent and intriguing years between 1775 and 1848.